Adverse event profile of five anti head and neck squamous cell carcinoma drugs: a descriptive analysis from WHO-VigiAccess - Gao, Weimin; Xia, Zhigang; Zhou, Tingfeng; Dong, Youlin (Frontiers in Pharmacology, 2025)
BackgroundHead and neck squamous cell carcinoma (HNSCC) remains a significant global health concern, with treatment outcomes for advanced or metastatic stages being suboptimal despite the availability of various targeted therapies and immunotherapies. This study evaluates five FDA-approved anti-HNSCC drugs—cetuximab, pembrolizumab, nivolumab, atezolizumab, and durvalumab—focusing on the adverse drug reactions (ADRs) associated with their use as reported in the WHO VigiAccess database.MethodsA retrospective analysis was conducted on ADR reports from the WHO-VigiAccess database, focusing on demographic information (age, gender, and geographical distribution) and ADR classification. The disproportionality analysis was used to identify ADRs through Reporting Odds Ratios (ROR) and Proportional Reporting Ratios (PRR). ADRs were categorized into 27 system organ classes (SOCs) for comparison across the five drugs.ResultsA total of 145,678 ADR reports were analyzed. Cetuximab exhibited the highest incidence of skin and subcutaneous tissue disorders (20.88%), while durvalumab showed elevated respiratory system disorders (18.53%). Pembrolizumab and nivolumab had notable immune-related adverse events, with malignant neoplasm progression reported at 5.56% and 4.23%, respectively. Atezolizumab was primarily associated with blood and lymphatic system disorders (5.51%). Disproportionality analysis revealed significant safety concerns for each drug, such as skin toxicity for cetuximab, respiratory complications for durvalumab, and reproductive system risks for nivolumab.ConclusionThis comparative pharmacovigilance study highlights the diverse safety profiles of the five anti-HNSCC drugs. Clinicians should consider these ADRs when treating patients, especially elderly individuals or those with comorbidities. Personalized monitoring strategies should be developed to minimize risks and optimize therapeutic outcomes for HNSCC patients.